Al-Quds Open University An Oasis in the Middle of Israeli Occupation - Barhoum, Dr. Musa Isa (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2026)
Al-Quds Open University (QOU) is a general Palestinian institution for higher education. It has an independent academic, financial and administrative sta tus. It provides distance learning and open education system, which encourage the learner to shoulder the responsibility. Al-Quds Open University system of education means, in essence, taking education to the work place or residence of interested learners, instead of requiring them to attend regular classes at a traditional campus, the matter that allows learners to study and work at the same time. During its establishment, the QOU went through three stages as follows: